2010
DOI: 10.1016/j.ijgo.2010.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum urinary retention after vaginal delivery

Abstract: Covert retention of urine was significantly associated with parturients who had an instrumental delivery and a duration of labor of more than 700 minutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
3
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 16 publications
3
65
3
5
Order By: Relevance
“…We also found that the PPUR incidence was higher in women who had perineal lacerations and episiotomy than in women who had none. Although, episiotomy, birth canal injury, and severe perineal lacerations were reported as being related to increased risk of urinary retention in some studies (10,17), in a recent cross-sectional study, these factors were not found to be effective in developing PPUR (16). However, we think that the pain caused by the repair of episiotomy or lacerations might result in reflex urethral spasm, and PPUR occurs subsequently.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…We also found that the PPUR incidence was higher in women who had perineal lacerations and episiotomy than in women who had none. Although, episiotomy, birth canal injury, and severe perineal lacerations were reported as being related to increased risk of urinary retention in some studies (10,17), in a recent cross-sectional study, these factors were not found to be effective in developing PPUR (16). However, we think that the pain caused by the repair of episiotomy or lacerations might result in reflex urethral spasm, and PPUR occurs subsequently.…”
Section: Discussionmentioning
confidence: 72%
“…We identified that a prolonged second stage of labor and delivery of macrosomic newborn were the risk factors associated with the occurrence of PPUR. Similarly, Kekre et al (16) reported that the lengths of the first and second stages of labor were directly related to postpartum urine residual volume, and labor duration ≥700 min was also associated with a greater incidence of PPUR. It is possible that mechanical strength applied to the pelvic muscle floor during prolonged second stage of labor, in addition to the rise in abdominal pressure with a macrosomic baby, may contribute to pelvic and pudendal nerve damage, resulting in neurologic impairment of micturition and, therefore, urinary retention.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Decrease in the adrenergic and cholinergic innervation of the bladder has been observed after induced urinary retention and bladder overdistension in rats (31,59). Whether women suffer neuroanatomic changes in the bladder with labor is unknown, although it is possible, since urinary retention is a well-known condition after childbirth, with epidural analgesia, prolonged labor, episiotomy, and high birth weight as risk factors (28,37,38). The epidural analgesia commonly used to avoid pain during labor causes bladder hypotonia and eliminates the normal sensation to void, leading to bladder overdistension (62), which may damage the detrusor and consequently induce long-term voiding difficulties (64).…”
Section: 56)mentioning
confidence: 99%
“…The incidence of PUR varies from 0.5 to 45% in women who have just delivered babies. This variability among studies may be due to an unclear definition for PUR (Kekre et al, 2011). PUR has been defined as the inability to void adequately within 6 h after delivery.…”
Section: Introductionmentioning
confidence: 99%